Cultural adaptation of the resilience scale for children in the Bellavista Elementary Educational Institution of UGEL Juliaca - Pineda Alcos, Verónica (2021)
Objective: To carry out a cultural adaptation of the Resilience Scale for Young People and Adults to aSchool Resilience Scale for children from 10 to 12 years old, which has validity and reliability, appliedto children of the fifth and sixth grade of the Bellavista Elementary Educational Institution of the city ofJuliaca, 2019. Methodology: This research corresponds to a quantitative approach, likewise a nonexperimentalcross-sectional design was used and it is of a psychometric type. The population includes168 fifth and sixth grade students from the Bellavista Elementary Educational Institution, whose agesrange from 10 to 12 years old. For data analysis, Aiken’s V statistics and Cronbach’s alpha were used.Results: Cronbach’s alpha coefficient of 0.732 was obtained, which indicates that the scale is highlyreliable. Conclusion: The cultural adaptation of the resilience scale for children shows good internalconsistency and construct validity.